O arauto da contra-revolução: o pensamento conservador de Plinio Corrêa de Oliveira (1968 1976) - Foresti, Luiz Felipe Loureiro (2013)
This dissertation seeks to undertake through immanent analysis of its production a study regarding the speech of Plinio Corrêa de Oliveira, the founder of the Sociedade Brasileira de Defesa da Tradição, Família e Propriedade (TFP), from 1968 to 1976, the harshest period of the dictatorship started in 1964 in Brazil. Polemicist of vast production, Oliveira had since 1968 a weekly column in the newspaper Folha de São Paulo, which served as a vehicle for spreading his ideas to a substantially larger audience than hitherto achieved by his writings. Before that, he has struggled since the 1930 s in order to set down a statement ruled by a Catholic thought of conservative bias able to reconfigure the society, and adapt it to the medieval way of life. However, in defense of these principles the author turns out to sanction the status quo conservation of the existing society. Inserted within this area of conservative thought, the author formulates judgments on major national and international issues of his time, denoting a unique and correct manner of action that would fit in his conception of Christian values. Thus we seek to understand the role of Plinio Correa as a conservative ideologist as well as the intervention strategies of the social organization he founded